Usage of Facebook in public libraries' promotion : the cases of Ireland and Croatia - Hebrang Grgić, Ivana; Mučnjak, Dorja (2012)
Since its launch in 2004, Facebook has become an important Web 2.0 service. Usage of Facebook has increased significantly – that is the reason why libraries often use the social network in promoting their activities. Firstly, we will give a short literature review (e. g. articles written by Lee King, Secker, Breeding and some others). Secondly, our paper and presentation will show the results of the study of Croatian and Irish public libraries on Facebook. Facebook is a good way of communicating between libraries and library users and we will try to find out how Irish and Croatian public libraries use the advantages of the social network. Lists of libraries for the study were found via Library.ie portal and via Croatian libraries on Facebook Facebook profile. The following criteria will be compared for a two-month period (September and October 2011): total number of Facebook fans or friends at the end of the period, connection between library’s web site and its Facebook profile/page (hyperlinks), number of library’s posts, number of friends’/fans’ posts, number of likes/comments to the posts, basic info about library, number of photos, number of likes/comments to the photos, number of discussions, number of events, number of notes, existence of privacy statements and some other. The results will show the usage of Facebook by Irish and Croatian librarians as well as their interaction with their users (fans or friends). The results will also indicate what public libraries in both countries could do to enhance library promotion on Facebook.
ENG